THE INFLUENCE OF THEOLOGY IN ISLAMIC EDUCATION THOUGHT - Muhammad Rusdi (At-Tazakki: Jurnal Kajian Ilmu Pendidikan Islam dan Humaniora, 2022)
Abstract: The purpose of the research on the influence of theology in Islamic educational thought is to analyze theological developments in the treasures of Islamic thought, analyze monumental figures and works of thought on theological developments in the treasures of Islamic thought and analyze traces of theological thought in Islamic educational thought. The research method (library research) is a literature study that contains a series of relevant theories related to the problems contained in the research. The sources of data for this research are books, scientific journals, and results that contain various studies and other sources. To obtain correct and precise results in analyzing data, the author uses content analysis techniques. Theology is a branch of science that discusses divinity. This study is of great interest to Muslims today. Where there will be debates between one understanding of theology with another. This difference in understanding of God ultimately resulted in the division of Muslims. Theology in Islam emerged after the death of the Prophet Muhammad. This flow of theology is divided into several firqohs. These firqohs are Shia, Khawarij, Muktazilah, Qadariyah, Jabariyah, Murji'ah, Ash'Ariyah and Maturiddiyah as a result of the Shiffin war. The theological differences are based on the backgrounds of their respective founders. The development of thought from the theologians then gave birth to several Muslim scientists engaged in education. With the development of science, it can be drawn as the influence of theology in Islamic educational thought. Keywords: Theology, Thought, Education.